2007
DOI: 10.5367/000000007780007344
|View full text |Cite
|
Sign up to set email alerts
|

Tourism Partnerships and Small Firms

Abstract: Partnerships have been a central feature of the tourism public policy landscape in advanced capitalist countries for some time. The intuitively appealing argument is that, by sharing expertise and decision making, commitment to the local tourism project is ensured. By participating in partnership working, small firms – which are almost universally characteristic of the sector – are said to contribute to the form and competitiveness of the tourism offer. Drawing on a variety of sources, this paper argu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…STBs in most sectors acted as agents of social cohesion, with a clear understanding that community support is necessary for business viability and enhancing the visitor experience. This finding is reflected in similar studies (Rubio-Andres et al 2019; Thomas 2007). Symbiotically, residents were positive about the presence of STBs in their communities, often assuming the role of ‘protectors’ of guests and conduits of valuable information for visitors.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…STBs in most sectors acted as agents of social cohesion, with a clear understanding that community support is necessary for business viability and enhancing the visitor experience. This finding is reflected in similar studies (Rubio-Andres et al 2019; Thomas 2007). Symbiotically, residents were positive about the presence of STBs in their communities, often assuming the role of ‘protectors’ of guests and conduits of valuable information for visitors.…”
Section: Discussionsupporting
confidence: 81%
“…However, the extent of STBs’ contribution to social cohesion and ensuring that an acceptable level of solidarity prevails is often mediated by the owner’s view of their locational and relational communities. Thomas (2007) observed that there is a direct relationship between small firm prosperity and the maintenance of an area’s current and future peace, and for that reason STB owners will strive to preserve the systems that solidify their communities. On the contrary, Acharya and Halpenny (2017) reported that among Nepalese homestay owners social cohesion was mediated by the locational-relational dichotomy, a caste system, the gendering of work and male and elite domination.…”
Section: Unpacking the Socio-cultural Sustainability Discourse And It...mentioning
confidence: 99%
“…Additionally, it helps to counter rural depopulation and benefits local society as business owners are more likely to be involved in cultural life and environmental conservation (Morrison et al, 2008). Lynch (2005), Getz and Petersen (2005), Shaw and Williams (2004) and Ateljevic and Doorne (2000) have all found evidence to suggest that tourism lifestyle entrepreneurs are not solely profit-oriented, and Thomas (2007) notes that they do not always fit traditional models of business activity. Their motivations are instead personal, centring on environmental values (Lynch, 2005); a drive to maintain a lifestyle and quality of life (Shaw & Williams, 2004;Ateljevic & Doorne, 2000); and more general risk-aversion (Getz & Petersen, 2005).…”
Section: Business "Style" and Impacts On The Local Economymentioning
confidence: 99%
“…The efficacy of the embedding process, at the level of the individual STF, is affected by power relations and local politics (Thomas, 2007) as well as by the business owner's personal networking and business skills. The literature identifies many advantages of embeddedness for rural businesses and given the importance of place for STFs; it is a key feature of their entrepreneurship.…”
Section: Rural In-migrants and Embeddednessmentioning
confidence: 99%
“…The community also has an important role in tourism development . The community will be encouraged to participate in tourism activities if the community knows the positive benefits of tourism (Suwantoro, 1997;Thomas, 2007). There are several development models of community-based empowerment, one of which is by increasing marketing and accessibility, improving quality and service through human resource development (Goodwin, 2002;Haywood, 1988;Timothy, 1999).…”
Section: Introductionmentioning
confidence: 99%